Rapid assessment methods in eye care: An overview - Srinivas Marmamula; Jill E Keeffe; Gullapalli N Rao (Indian Journal of Ophthalmology, 2012)
Reliable information is required for the planning and management of eye care services. While classical research methods provide reliable estimates, they are prohibitively expensive and resource intensive. Rapid assessment (RA) methods are indispensable tools in situations where data are needed quickly and where time- or cost-related factors prohibit the use of classical epidemiological surveys. These methods have been developed and field tested, and can be applied across almost the entire gamut of health care. The 1990s witnessed the emergence of RA methods in eye care for cataract, onchocerciasis, and trachoma and, more recently, the main causes of avoidable blindness and visual impairment. The important features of RA methods include the use of local resources, simplified sampling methodology, and a simple examination protocol/data collection method that can be performed by locally available personnel. The analysis is quick and easy to interpret. The entire process is inexpensive, so the survey may be repeated once every 5-10 years to assess the changing trends in disease burden. RA survey methods are typically linked with an intervention. This article provides an overview of the RA methods commonly used in eye care, and emphasizes the selection of appropriate methods based on the local need and context.